Therapeutic Strategies Targeting Mitochondrial Calcium Signaling: A New Hope for Neurological Diseases? - Laura R. Rodríguez; Tamara Lapeña-Luzón; Noelia Benetó; Vicent Beltran-Beltran; Federico V. Pallardó; Pilar Gonzalez-Cabo; Juan Antonio Navarro (MDPI AG, 2022)
Calcium (Ca2+) is a versatile secondary messenger involved in the regulation of a plethora of different signaling pathways for cell maintenance. Specifically, intracellular Ca2+ homeostasis is mainly regulated by the endoplasmic reticulum and the mitochondria, whose Ca2+ exchange is mediated by appositions, termed endoplasmic reticulum-mitochondria-associated membranes (MAMs), formed by proteins resident in both compartments. These tethers are essential to manage the mitochondrial Ca2+ influx that regulates the mitochondrial function of bioenergetics, mitochondrial dynamics, cell death, and oxidative stress. However, alterations of these pathways lead to the development of multiple human diseases, including neurological disorders, such as amyotrophic lateral sclerosis, Friedreich's ataxia, and Charcot-Marie-Tooth. A common hallmark in these disorders is mitochondrial dysfunction, associated with abnormal mitochondrial Ca2+ handling that contributes to neurodegeneration. In this work, we highlight the importance of Ca2+ signaling in mitochondria and how the mechanism of communication in MAMs is pivotal for mitochondrial maintenance and cell homeostasis. Lately, we outstand potential targets located in MAMs by addressing different therapeutic strategies focused on restoring mitochondrial Ca2+ uptake as an emergent approach for neurological diseases.